Symbiont composition and coral genotype determines massive coral species performance under end-of-century climate scenarios - Klepac, Courtney N.; Eaton, Katherine R.; Petrik, Chelsea G.; Arick, Lindsay N.; Hall, Emily R.; Muller, Erinn M. (Frontiers in Marine Science, 2023)
The recent decline of coral health and substantial loss of coral cover along Florida’s Coral Reef (FCR) results from local stressors such as degraded water quality and disease outbreaks in addition to anthropogenically driven global stressors including ocean warming and acidification. Intervention strategies intended for the restoration of degraded reef habitats need a better understanding of the influence of ocean warming and acidification on coral health to target coral species and individual genotypes that may be more resistant or resilient to such stressors. Here, we examined a suite of physiological traits (coral host and algal symbiont) in response to experimentally elevated water temperatures and pCO2 levels, both separately and in concert, using threatened reef-building corals Pseudodiploria clivosa and Orbicella faveolata reared within a land-based coral nursery. After two months of exposure, responses differed by coral species, where P. clivosa showed declined physiology in response to combined ocean warming and acidification stress and ocean warming alone, whereas O. faveolata showed a positive response under ocean acidification. Responses to temperature could be associated with the algal symbionts harbored, as P. clivosa was dominated by the thermally sensitive Breviolum, and O. faveolata was dominated by the thermally tolerant Durusdinium. Additionally, corals were raised in well-sourced seawater that was naturally high in pCO2, which could have led to corals acclimating to acidified conditions. Of the three P. clivosa genets tested, we determined a top-performing genotype under the combined warming and acidification treatment. O. faveolata, however, displayed high genet variation by treatment and phenotypic trait, making genotype performance rankings challenging to discern. The evidence provided in this study demonstrates that high phenotypic variation in nursery-reared corals contributes to variable warming-acidification responses, suggesting that high-standing genetic variation in nursery-reared corals could support diverse coral restoration population outcomes along FCR.